Ecophysiological responses of two ecotypes of Dactylis glomerata L. under water-deficit conditions - Kostopoulou P.; Karatassiou M.; Abraham E.M.; Parissi Z.M.; Kyriazopoulos A.P.; Kapsali E. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
Development of improved water-saving varieties is a high priority in forage grass breeding programs especially if the climate change predictions for the Mediterranean region become true. In this experiment the adaptation responses of two ecotypes of Dactylis glomerata L., one from a fir forest and the other from an adjacent open grassland, to water-deficit conditions were studied. Plants of these ecotypes were planted into pots and subjected during the growing season to two water supplies: (i) well-watered conditions; and (ii) rainfed conditions. Leaf water potential, relative water content, assimilation rate, stomatal conductance, transpiration rate and water use efficiency were assessed at seven-day intervals during the experimental period. Both water regime and ecotype were found to play some role in the ecophysiological responses of D. glomerata to water shortage. Under the conditions of moderate water stress of the present experiment, the forest ecotype showed a drought resistance behaviour, maintaining its photosynthetic efficiency. On the contrary the grassland ecotype showed a drought avoidance behaviour, limiting transpirational loss through stomatal closure, negatively affecting its photosynthetic capacity.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)